DEFINITIVE CHANGES OF THE TERM "AUTHENTIC" IN THE CONTEXT OF BULGARIAN FOLKLORE CULTURE - Kardzhieva, Mariya (E-Journal VFU, 2026)
The text in the current publication explores the essence of the concept of "authenticity" in the context of the contemporary lifestyle and its characteristic dynamics of processes. Conceptual focuses are directed toward Bulgarian folklore, using the National Folklore Fair in Koprivshtitsa as a model. The arguments logically trace the changes in rural life and culture from the end of the 19th century to the present day, thereby defending the thesis of the "purity" of the folklore tradition presented at the 1986 Fair, due to the living connection of that generation with the primary source. The shifts in the understanding of authenticity are tracked, which today is defined as "local identity" and "revitalized heritage," recognized by a UNESCO convention. It is established that: 1) folklore changes under the influence of globalization but preserves its value as a modern form of cultural continuity; and 2) the etymological reference proves that today authenticity is not an imitation of the past, but a living transformation of folk art.